Preoperative nomogram for identifying invasive pulmonary adenocarcinoma in patients with pure ground-glass nodule: A multi-institutional study - She, Yunlang (Oncotarget, 2016)
PURPOSE: To construct a preoperative nomogram to differentiate invasive pulmonary adenocarcinomas (IPAs) from preinvasive lesions in patients with solitary pure ground-glass nodules (GGN). METHODS: A primary cohort of patients with pathologically confirmed pulmonary solitary pure GGN after surgery were retrospectively studied at five institutions from January 2009 to September 2015. Half of the patients were randomly selected and assigned to a model-development cohort, and the remaining patients were assigned to a validation cohort. A nomogram predicting the invasive extent of the solitary GGNs was constructed based on the independent risk factors. Predictive performance was evaluated by concordance index (C-index) and calibration curve. RESULTS: Out of 898 cases included in the study, 501 (55.8%) were preinvasive lesions and 397 (44.2%) were IPAs. In the univariate analysis, lesion size (p < 0.001), lesion margin (p = 0.041), lesion shape (p < 0.001), mean computed tomography (CT) value (p = 0.018), presence of pleural indentation (p = 0.017), and smoking status (p = 0.014) were significantly associated with invasive extent. In multivariate analysis, lesion size (p < 0.001), lesion margin (p = 0.042), lesion shape (p < 0.001), mean CT value (p = 0.014), presence of pleural indentation (p = 0.026), and smoking status (p = 0.004) remained the predictive factors of invasive extent. A nomogram was developed and validation results showed a C-index of 0.94, demonstrating excellent concordance between predicted and observed results. CONCLUSIONS: We established and validated a novel nomogram that can identify IPAs from preinvasive lesions in patients with solitary pure GGN.